Discontinuation of anti-PD-1 antibody therapy in the absence of disease progression or treatment limiting toxicity: clinical outcomes in advanced melanoma. (28th March 2019) - Jansen, Y J L; Rozeman, E A; Mason, R; Goldinger, S M; Geukes Foppen, M H; Hoejberg, L; Schmidt, H; van Thienen, J V; Haanen, J B A G; Tiainen, L; Svane, I M; Mäkelä, S; et al.
Abstract: Background: Programmed cell death protein 1 (PD-1) blocking monoclonal antibodies improve the overall survival of patients with advanced melanoma but the optimal duration of treatment has not been established. Patients and Methods: This academic real-world cohort study investigated the outcome of 185 advanced melanoma patients who electively discontinued anti-PD-1 therapy with pembrolizumab ( N  =   167) or nivolumab ( N  =   18) in the absence of disease progression (PD) or treatment limiting toxicity (TLT) at 14 medical centres across Europe and Australia. Results: Median time on treatment was 12 months (range 0.7–43). The best objective tumour response at the time of treatment discontinuation was complete response (CR) in 117 (63%) patients, partial response (PR) in 44 (24%) patients and stable disease (SD) in 16 (9%) patients; 8 (4%) patients had no evaluable disease (NE). After a median follow-up of 18 months (range 0.7–48) after treatment discontinuation, 78% of patients remained free of progression. Median time to progression was 12 months (range 2–23). PD was less frequent in patients with CR (14%) compared with patients with PR (32%) and SD (50%). Six out of 19 (32%) patients who were retreated with an anti-PD-1 at the time of PD obtained a new antitumour response. Conclusions: In this real-world cohort of advanced melanoma patients discontinuing anti-PD-1 therapy in the absence of TLT or PD, the duration of anti-PD-1 therapy was shorter when compared with clinical trials. In patients obtaining a CR, and being treated for >6 months, the risk of relapse after treatment discontinuation was low. Patients achieving a PR or SD as best tumour response were at higher risk for progression after discontinuing therapy, and defining optimal treatment duration in such patients deserves further study. Retreatment with an anti-PD-1 at the time of progression may lead to renewed antitumour activity in some patients. Clinical trial registration: NCT02673970 (https://clinicaltrials.gov/ct2/show/NCT02673970?cond=melanoma&cntry=BE&city=Jette&rank=3 )